Assessing essentiality of nickel in growing Hariana heifers by determining its effect on performance, nitrogen and mineral metabolism, urease activity, and endocrine biomarkers - KUMAR, MUNEENDRA; SINGH, ANUJ; KUMAR, VINOD; KUSHWAHA, RAJU; VASWANI, SHALINI; KUMAR, AVINASH; SHUKLA, PANKAJ KUMAR; SINGH, YAJUVENDRA (The Indian Journal of Animal Sciences, 2022)
The objective of this study was to determine the effect of nickel (Ni) on growth performance, nutrient utilization, urease activity, and endocrine variables in growing cattle. Growing Hariana heifers (18) were randomly assigned into three groups (n=6), i.e. groups either without Ni supplementation (Ni0.0; control) or supplemented with 1.5 mg of Ni/kg DM (Ni1.5), and 3.0 mg of Ni/kg DM (Ni3.0). The experiment lasted for 90 days. Heifers supplemented with Ni showed higher nutrient intake and average daily gain (ADG) than control group. The nutrient digestibility was not affected by treatment, while the Ni supplemented animals showed higher intake, excretion, and nitrogen balance. The urease activity was comparable and higher in the Ni1.5 and Ni3.0 groups than in the control group. There was no effect of treatment on the metabolism of calcium (Ca), phosphorus (P), zinc (Zn), copper (Cu), and chromium (Cr). However, iron (Fe) retention showed a negative association with Ni levels. Plasma cortisol concentration was lower while the insulin like growth factor-1 (IGF-1) and tetraiodothyronine (T4) were higher in the Ni3.0 group compared to the Ni0.0 group, with Ni1.5 being intermediate. The plasma concentrations of triiodothyronine (T3) and thyroid stimulating hormone (TSH) were not affected by dietary treatment. Plasma Ni concentration showed a dose dependent increase whereas, plasma levels of other minerals were not affected by treatment. In conclusion, dietary Ni supplementation in growing Hariana heifers improves performance and nutrient utilization by modulating urease activity and endocrine growth biomarkers.